Diagnostics of primary school teachers’ creative potential in Kazakhstan - Alsitova, Assemgul; Kuzembayeva, Gulzhana; Zhazykova, Makpal; Maydangalieva, Zhumagul (Journal of Education and e-Learning Research, 2024)
A teacher’s creative potential (CP) is recognised as an integrative personality trait that includes the ability to develop innovative teaching ideas, find practical solutions to non-standard teaching tasks, select the most effective methods for engaging in creative pedagogical activities and contribute to the development of students’ creativity. The purpose of the study is to identify the primary school teachers’ level of CP and to explore barriers to its development. The study employed a mixed-methods research design, analyzing both qualitative and quantitative data collected by means of a survey and interviews with primary school teachers. The literature review has shown that teachers may foster their students’ creativity if they have the necessary CP, ample knowledge, resources and tools, apply creativity-development techniques and create an environment that encourages creative collaboration. The survey’s results showed that across all age groups and qualification levels, primary teachers’ CP development was at a medium level. The interviews revealed the conditions and barriers to CP development such as psycho-emotional and educational factors and resources. The study findings will contribute to further comprehension and improvement of teachers’ CP development in higher and vocational education.